Peran Janus Kinase inhibitor pada Penyakit Autoimun - Nugroho Nitiyoso (PT Kalbe Farma Tbk., 2022)
Modalitas pengobatan utama penyakit autoimun adalah obat immunosupresif, misalnya methotrexate, TNFi-biologics, non-TNFi-biologics, dan yang paling baru adalah Janus Kinase inhibitor. Mekanisme kerja Janus Kinase inhibitor adalah dengan cara menghambat kerja enzim Janus Kinase pada proses signaling respons imun. Dalam artikel ini akan dibahas beberapa obat Janus Kinase inhibitor seperti: tofacitinib, baricitinib, upadacitinib, dan filgotinib, serta peran obat-obat ini pada pengobatan penyakit autoimun. The main treatment modality for autoimmune disease is immunosuppressive drugs, eg methotrexate, TNFi-biologics, non-TNFi-biologics, and most recently Janus Kinase inhibitors. The mechanism of action of Janus Kinase inhibitor drugs is by inhibiting the action of the Janus-Kinase enzyme in the signaling process of the immune response. This article will discuss several Janus Kinase inhibitor drugs such as: tofacitinib, baricitinib, upadacitinib, and filgotinib, as well as their role in the treatment of autoimmune diseases.